(3TQW GdEVGaI GdTGajI deG YfO GdTjN JjSjQs - (3eMeO GdYQGajs
(3ChdgG (B:s
(3GdMeO ddg hddEeGe SjOi eMeO GdYQGbi ai TQW GdEVGaI GdTGajI deG YfO GdTjN JjSjQ TQW GdTGajI Cf jchf Hjf WQajgG aGYdef s
(3BNQgG (B:s
(3hGdNHQ eMPha heG ehUhdg hRjO NHQkG eHJOC eMPha GfJgi s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH(B3s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3eUOQ GbJfGA GdCUd (B:s
(3GdQHGW (B(489(3O(B) s
Keywords: (3GdeLGejYs